Preservation of cyclophosphamide-compromised fertility in female mice by tocotrienol supplementation / Hazar Shakir Saleh - Saleh, Hazar Shakir (Institute of Graduate Studies, UiTM, 2015)
Cyclophosphamide (CPA) chemotherapy has been known to cause ovarian failure. CPA therapy leads to infertility via oxidative stress induced apoptosis of ovarian cells. Tocotrienols (T3), vitamin E isoform, is a much more potent antioxidant compared to tocopherols. T3 is a potent antioxidant and anti-inflammatory agent. The role of T3 in ovarian protection throughout chemotherapy remains unelucidated, hence this study has been undertaken to investigate the role of T3 in the maintenance of normal female reproductive system from temporal infertility due to CPA administration. The alteration and regulation of ER and PR, genes and proteins, expression were investigated to ascertain the deleterious effect of CPA and whether co-administration with T3 showed any difference. That was hoped to explain the involvement of ER and PR signaling pathway as biomarker in maintaining fertility during chemotherapy treatment. 60 female ICR mice, aged between 8 to 10 weeks were divided into 5 treatment groups: CPA, CPA&T3, normal saline, T3 only, and corn oil only. The treatment was given for 30 consecutive days, followed by administration of pregnant mare serum gonadotrophin and human chorionic gonadotrophin to induce super ovulation. The mice were sacrificed at 14 to 16 hours post induction, after which all animal were euthanized…